2009 ICSE Workshop on Emerging Trends in Free/Libre/Open Source Software Research and Development 2009
DOI: 10.1109/floss.2009.5071359
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study on selection of Open Source Software - Preliminary results

Abstract: Growing attention on component-based development has inspired the development of several normative methods for selection of software components. Despite these efforts, empirical studies show only minor adoption of such methods. To understand how research can contribute to improving the selection of components we interviewed developers from 16 Norwegian software companies which integrate Open Source Software (OSS) components into their systems. We find that the selection of OSS components has a situational natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 17 publications
0
26
0
1
Order By: Relevance
“…Programmers composed the majority of the group: 73% of the group works with IT, 92% [7][10] [9] selection happens in early development phases [10] selection can happen in any phase, based on project context & flexibility [12] evidences of real component usage matters on decision [10] comply to functional requirements and project constraints [7][10] [11] future support assurance matters on decision [6][10][9] bring less effort and take less time to apply matters on decision [6] licensing terms matters on decision [11] 1304 PROCEEDINGS OF THE FEDCSIS. PRAGUE, 2017 read and write in English, 38% code some days every week and 31% code on a daily basis; 69% informed that are familiar to JavaScript language and CSS, and 92% are familiar to HTML.…”
Section: Prototype Focus Group and Heuristic Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Programmers composed the majority of the group: 73% of the group works with IT, 92% [7][10] [9] selection happens in early development phases [10] selection can happen in any phase, based on project context & flexibility [12] evidences of real component usage matters on decision [10] comply to functional requirements and project constraints [7][10] [11] future support assurance matters on decision [6][10][9] bring less effort and take less time to apply matters on decision [6] licensing terms matters on decision [11] 1304 PROCEEDINGS OF THE FEDCSIS. PRAGUE, 2017 read and write in English, 38% code some days every week and 31% code on a daily basis; 69% informed that are familiar to JavaScript language and CSS, and 92% are familiar to HTML.…”
Section: Prototype Focus Group and Heuristic Resultsmentioning
confidence: 99%
“…This research aims to go beyond a new rational method for component selection, aggregating info on how this activity is done, a fundamental step to design a successful tool with this purpose [7] [10]. There are only a few studies focusing on gathering Industry feedback, which is one of the purposes of this study, and bring more evidences of real component selection practice.…”
Section: Discussionmentioning
confidence: 99%
“…A critical success factor in CBSD is the selection of appropriate OSS products, and both researchers and industry have proposed a variety of OSS evaluation and selection methods [18]. However, studies have also shown that practitioners typically do not use these "normative" selection methods [19,20]. Hauge et al observed a first fit rather than a best fit strategy [19].…”
Section: Component-based Development With Open Source Softwarementioning
confidence: 99%
“…However, studies have also shown that practitioners typically do not use these "normative" selection methods [19,20]. Hauge et al observed a first fit rather than a best fit strategy [19].…”
Section: Component-based Development With Open Source Softwarementioning
confidence: 99%
“…Although the majority of published works have a non OSS-related rationale, some researchers have started to collect evidence specifically related to OSS systems. Among these late emerging areas, the topics of OSS components and architectures have been investigated both within research works [27,18,8,25], and through specifically funded EU projects (QualiPSo 2 -Quality Platform for Open Source Software and QUALOSS 3 -QUALity in Open Source Software). This research directly responds to the need of identifying and extracting existing OSS components [2], or of providing options for choosing the best OSS component for inclusion in a software system [18].…”
Section: Background and Related Workmentioning
confidence: 99%